2018
DOI: 10.1523/eneuro.0092-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Key Brain Network Nodes Show Differential Cognitive Relevance and Developmental Trajectories during Childhood and Adolescence

Abstract: Human adolescence is a period of rapid changes in cognition and goal-directed behavior, and it constitutes a major transitional phase towards adulthood. One of the mechanisms suggested to underlie the protracted maturation of functional brain networks, is the increased network integration and segregation enhancing neural efficiency. Importantly, the increasing coordinated network interplay throughout development is mediated through functional hubs, which are highly connected brain areas suggested to be pivotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 84 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…Adolescence is a time of profound and genetically mediated changes in whole-brain network organization [1][2][3][4][5][6][7] . Adolescent development is important for overall maturation in cognitive and educational functions and brain health more generally, a notion reinforced by the overlapping onset of several neurodevelopmental and psychiatric disorders [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a time of profound and genetically mediated changes in whole-brain network organization [1][2][3][4][5][6][7] . Adolescent development is important for overall maturation in cognitive and educational functions and brain health more generally, a notion reinforced by the overlapping onset of several neurodevelopmental and psychiatric disorders [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al have found using the graph theory in the (10-20) age range, the connection between the CN centers and the connection between the cortical regions increased from adolescence to adulthood. 59 As a result of the studies, it was observed that there was a significant decrease in the centrality of the thalamus and cerebellum among the subcortical components and it showed increasing activation with age. They showed that the CN shows a weak network connection, within-network connectivity and between-network connectivity and decreases with age.…”
Section: Discussion For Cerebellar Networkmentioning
confidence: 94%
“…58 Kolskar et al looked at the age range of (8-22) years in their work with fMRI during rest and task performance, DMN, cingulo-opercular, visual, subcortical components (bilateral putamen, bilateral thalamus, and cerebellum), frontoparietal-related components and sensorimotor network nodes and examined age-related differences with ICA. 59 As a result of the studies, it was observed that there was a significant decrease in the centrality of the thalamus and cerebellum among the subcortical components and it showed increasing activation with age.…”
Section: Discussion For Cerebellar Networkmentioning
confidence: 94%
See 2 more Smart Citations